The TNFR1 Antagonist Atrosimab Is Therapeutic in Mouse Models of Acute and Chronic Inflammation - Richter, Fabian; Williams, Sarah K.; John, Katharina; Huber, Carina; Vaslin, Camille; Zanker, Henri; Fairless, Richard; Pichi, Kira; Marhenke, Silke; Vogel, Arndt; Dhaen, Marie-Ann; Herrmann, Stefanie; et al. (Frontiers in Immunology, 2021)
Therapeutics that block tumor necrosis factor (TNF), and thus activation of TNF receptor 1 (TNFR1) and TNFR2, are clinically used to treat inflammatory diseases such as rheumatoid arthritis, inflammatory bowel disease and psoriasis. However, TNFR1 and TNFR2 work antithetically to balance immune responses involved in inflammatory diseases. In particular, TNFR1 promotes inflammation and tissue degeneration, whereas TNFR2 contributes to immune modulation and tissue regeneration. We, therefore, have developed the monovalent antagonistic anti-TNFR1 antibody derivative Atrosimab to selectively block TNFR1 signaling, while leaving TNFR2 signaling unaffected. Here, we describe that Atrosimab is highly stable at different storage temperatures and demonstrate its therapeutic efficacy in mouse models of acute and chronic inflammation, including experimental arthritis, non-alcoholic steatohepatitis (NASH) and experimental autoimmune encephalomyelitis (EAE). Our data support the hypothesis that it is sufficient to block TNFR1 signaling, while leaving immune modulatory and regenerative responses via TNFR2 intact, to induce therapeutic effects. Collectively, we demonstrate the therapeutic potential of the human TNFR1 antagonist Atrosimab for treatment of acute and chronic inflammatory diseases.